THE ROLE OF SCHOOL IN PARENTAL INVOLVEMENT IN THE USA - Bezrukova, Anna (Studies in Comparative Education, 2017)
The article defines the role of supporting and encouragement of parents by teachers to participate in the educational process. The purpose of this study is to investigate the perceptions and experiences of teachers in supporting parents. The author gives theoretical frameworks and models of parental involvement in school. It highlights the role of the school in the system of formation of parents’ pedagogical knowledge and culture. The analysis of recent works and publications showed that parental involvement increases academic grades, attendance, leadership skills, graduation rates, self-esteem, esteem among parents and students, and more positive attitudes in school.The aim of the article is to investigate the role of school in parental involvement and define factors that influence parent-school relation-ships.Numerous studies show how this relationship works. Over the last 20 years Vanderbilt University and John Hopkins University have sponsored the majority of the research on parent involvement.The essential elements from the research work of Epstein, Hoover-Dempsey and Harris include simple steps that schools can implement: welcome parents as volunteers, provide opportunities for parents to learn how to help their children develop academically and behaviorally, achieve social and emotional success, maintain close links of communication between family and school and provide opportunities for parents to be full partners in making decisions directly affecting students.